KEPASTIAN HUKUM DALAM PEMERIKSAAN PERKARA SECARA IN ABSENTIA TERHADAP TINDAK PIDANA DESERSI DI HUBUNGKAN DENGAN ASAS PERADILAN YANG SEDERHANA, CEPAT DAN BIAYA RINGAN - Sunti Sundari (Scientia Regendi, 2021)
The criminal act of desertion in absentia is in accordance with Article 143 of Law Number 31 of 1997 concerning military justice which explains the examination of desertion cases in absentia in which the defendant has fled and has not been found again within 6 (six) months of being transferred to court and efforts have been made summoning 3 (three) times in a row legally, but not attending the trial without a reason can be terminated without the presence of the defendant. The problems are: How is the application of Article 143 of Law Number 31 of 1997 to desertion cases connected in absentia to the simple, fast and low cost trial principle? and what are the obstacles in the handling of cases of desertion in absentia in the Military Courts? The approach method used by the author in this research is juridical empirical, research specification with descriptive analysis, data sources from: secondary data, primary data and tertiary data, so the analysis method is qualitative. The results of the study show that the time limit for examining desertion cases in absentia in practice in the field is that there are differences in interpretation by military judges, some are more than six months and some are less than six months, so that there is no uniformity in legal certainty, it is necessary to have SEMA. which regulates a three-month time limit for uniform legal certainty as well as realizing simple, fast and low cost trial principles. Keywords: Military, criminal act, desertion, in absentia, court.